Imperative Sentences in swearing of Bengkulu-Malay Language - Rustinar, Eli; Sobarna, Cece; Wahya, Wahya; Djajasudarma, Fatimah T. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Swearing is the harsh words, that is expressed by humans to show their anger, resentment or disappointment. The research method was descriptive qualitative. The Data was the swear expressed by the informant speakers. The collecting data used the referring method and introspection method with tapping technique using record with the technique tools recorded on the data card. The data analysis used the equivalent and distribution method. The result of the research showed from eleven swearing imperative sentences, there were eight swearing imperative sentences that contained commands, there were two swearing imperative sentences that contained requests, and one swearing imperative sentence that contained an invitation.